DNA Blocks the Lethal Effect of Human Beta-Defensin 2 Against Neisseria meningitidis - Wassing, Gabriela M.; Lidberg, Kenny; Sigurlásdóttir, Sara; Frey, Jonas; Schroeder, Kristen; Ilehag, Nathalie; Lindås, Ann-Christin; Jonas, Kristina; Jonsson, Ann-Beth (Frontiers in Microbiology, 2021)
Neisseria meningitidis is a gram-negative bacterium that often asymptomatically colonizes the human nasopharyngeal tract. These bacteria cross the epithelial barrier can cause life-threatening sepsis and/or meningitis. Antimicrobial peptides are one of the first lines of defense against invading bacterial pathogens. Human beta-defensin 2 (hBD2) is an antimicrobial peptide with broad antibacterial activity, although its mechanism of action is poorly understood. Here, we investigated the effect of hBD2 on N. meningitidis. We showed that hBD2 binds to and kills actively growing meningococcal cells. The lethal effect was evident after 2 h incubation with the peptide, which suggests a slow killing mechanism. Further, the membrane integrity was not changed during hBD2 treatment. Incubation with lethal doses of hBD2 decreased the presence of diplococci; the number and size of bacterial microcolonies/aggregates remained constant, indicating that planktonic bacteria may be more susceptible to the peptide. Meningococcal DNA bound hBD2 in mobility shift assays and inhibited the lethal effect of hBD2 in a dose-dependent manner both in suspension and biofilms, supporting the interaction between hBD2 and DNA. Taken together, the ability of meningococcal DNA to bind hBD2 opens the possibility that extracellular DNA due to bacterial lysis may be a means of N. meningitidis to evade immune defenses.